Peningkatan Efisiensi Distilasi Air Energi Surya Jenis Bak Menggunakan Pengapung Silinder Berkain - Alexander Franclean; FA. Rusdi Sambada (LPPM Universitas Putera Batam, 2022)
Basin type solar water distillation has a problem, namely low efficiency. One of the factors causing the low efficiency of basin type solar water distillation is the long evaporation process. The long evaporation process is caused by the large mass of water in the distillation bath. Enlarging the absorber area with materials with capillary properties, such as cloth, is one way to increase efficiency. Enlarging the absorber area can be done by adding a cloth cylinder float. This study aims to increase the efficiency of tub-type solar energy water distillation using a cylindrical cloth float. The study was conducted indoors using a distillation model with an area of ​​0.1 m2. As a solar energy simulator, heating lamps are used. The variables that varied in this study were the mass of water in the tub of 0.6 kg, 1 kg and 1.5 kg, and the number of cloth floats was 3, 6 and 12. Data were collected every 10 seconds for 2 hours using sensors and microcontrollers for each variation. The variables measured were absorber temperature, TA (°C), cover glass temperature, TK (°C) and the volume of water produced, m (litres). The results showed that the variation of the number of floats as many as 12 pieces with a mass of water in the tub as much as 0.6 kg produced the most distilled water, namely 99 ml for 2 hours or 0.47 litres/(hour.m2) with an efficiency of 42%